The quest for coherent climate governance and the importance of linking emissions trading schemes. (June 2022) - Kelly, Gerard
A diverse range of regulatory schemes in climate policy has produced a fragmented and crowded governance landscape. Devising pathways towards converging all of the different climate governance approaches would be a Herculean task, but it is argued here that this should not inhibit efforts to scale up regulatory initiatives in specific areas of climate governance. In this respect, it is argued that linking emissions trading schemes (ETSs) would significantly contribute to the development of creating more durable and connected climate governance arrangements. At present, the global expansion of ETSs raises risks of potential regulatory divergence, conflict, and the emergence of a disconnected patchwork of schemes. However, the expansion of trading schemes has also brought an increased interest in the feasibility of linkage between ETSs. This opinion argues that, in the absence of a comprehensive multilateral regime governing emissions trading, policymakers and scholars must instead refocus on the challenges of creating a coherent climate governance architecture from the bottom-up. It further suggests that the development and implementation of durable linkages between ETSs are critical building blocks in this quest.